2019
DOI: 10.1097/md.0000000000017508
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of proximal tibial morphology in northeast Chinese population based on three-dimensional reconstruction computer tomography

Abstract: Tibial component of total knee arthroplasty (TKA) is designed according to morphology of proximal tibia to a large extent. Owing to racial difference, current design of tibial component based on Caucasian may not be suitable for Chinese patients. Meanwhile, data of proximal tibial morphology in Chinese population is lacking. The objective of this research was to investigate proximal tibial morphology of northeast Chinese population.Computer tomography (CT) image of 164 northeast Chinese participants was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Therefore, the stable fixation of the fragment could be achieved by the strong support of the filled calcium sulfate bone graft substitute and the rigid fixation of screws or plates. The mean TPA at the final follow-up was 9.7°± 3.5°compared to the normal northeast Chinese lateral TPA of 8.44°± 2.76°, and no posterolateral instability of the knee joint was found, which implies that the fixation was rigid enough, and no significant subsidence of the articular fracture fragments happened after a full weight-bearing activities [26].…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the stable fixation of the fragment could be achieved by the strong support of the filled calcium sulfate bone graft substitute and the rigid fixation of screws or plates. The mean TPA at the final follow-up was 9.7°± 3.5°compared to the normal northeast Chinese lateral TPA of 8.44°± 2.76°, and no posterolateral instability of the knee joint was found, which implies that the fixation was rigid enough, and no significant subsidence of the articular fracture fragments happened after a full weight-bearing activities [26].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, the mean TT-PCL distance was 19.2 ± 4.3 mm, which was smaller than the previous measurement based on 3D models [ 19 ]. The difference may be caused by the factor of ethnicity [ 30 ]. An optimal cut-off value (19 mm) of TT-PCL distance was found in the safe zone (-5°-10°) to combine the selection of the Akagi line and MTTT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the geometric ratios of four commonly implanted tibial baseplates could accommodate a large proportion of the observed morphologic variability, it is important to note that a surgeon generally only uses one or a few TKA brands, which makes it diicult to avoid bone-implant mismatch in all knees. Tibial AP and ML dimensions are signiicantly diferent among men and women, and between races [1,2,9,10,18,26,30,33,37,41,43,50,53]. One study found a strong correlation between the ML width and AP length at the medial and lateral compartments, but observed minimal diferences in correlations on the basis of sex and race [13].…”
Section: Discussionmentioning
confidence: 99%